2021
DOI: 10.3390/agronomy11061224
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Errors of Semi-Mechanized Coffee Planting by Remotely Piloted Aircraft

Abstract: Mechanized operations on terrain slopes can still lead to considerable errors in the alignment and distribution of plants. Knowing slope interference in semi-mechanized planting quality can contribute to precision improvement in decision making, mainly in regions with high slope. This study evaluates the quality of semi-mechanized coffee planting in different land slopes using a remotely piloted aircraft (RPA) and statistical process control (SPC). In a commercial coffee plantation, aerial images were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…On small size mountain vineyards and hilly areas, spraying pesticides with UAVs showed higher efficiency. Sarri found that the working capacity of an UAV was 2-fold that of a sprayer gun, and 1.6-fold that of a knapsack sprayer [16,17]. These results showed that UAVs spraying pesticide have a more efficient spraying efficiency.…”
Section: Introductionmentioning
confidence: 94%
“…On small size mountain vineyards and hilly areas, spraying pesticides with UAVs showed higher efficiency. Sarri found that the working capacity of an UAV was 2-fold that of a sprayer gun, and 1.6-fold that of a knapsack sprayer [16,17]. These results showed that UAVs spraying pesticide have a more efficient spraying efficiency.…”
Section: Introductionmentioning
confidence: 94%
“…As noted, regions with slopes above 20% are overestimated. In areas with this characteristic, control points on the soil are necessary, which reduces error levels to the geodetic precision level in [55]. It is important to consider the overestimated errors, as this can lead to a reduction in areas suitable for mechanized planting.…”
Section: Precision Of Digital Surface Modelsmentioning
confidence: 99%
“…In contrast, treatment and management of the cultures and the behavior of the plant in this initial stage will be crucial for its future development and, consequently, the crop's productivity. Thus, the use of precision and digital agriculture data by RPAS is promising and applicable in the context of studies and development of the coffee culture, as evidenced in coffee studies by Chemura et al [7], Oliveira et al [8], Santos et al [5], Marin et al [9], Santana et al [10], and Barbosa et al [11]. Studies on plant development are strongly correlated with lifespan, seed mass, and ability to compete for light [12]; however, despite the simplicity of measurement, these can be time-consuming to collect in the field, especially in studies with large areas.…”
Section: Introductionmentioning
confidence: 99%